Critical care pharmacy in Saudi Arabia: Historical evolution and future directions—A review by the Critical Care and Emergency Medicine Pharmacy Specialty Network at the Saudi Society of Clinical Pharmacy. Issue 11 (12th September 2021) - Alshaya, Abdulrahman I.; Alhammad, Abdullah M.; Ismail, Nadia; Alkhani, Nada; Alharbi, Shmeylan; Alenazi, Ahmed O.; Aljuhani, Ohoud
Abstract: Background: Clinical pharmacy services in Saudi Arabia (SA) have improved over the past few years, leading to improved patient‐centered outcomes. Clinical pharmacy services have been steadily incorporating critical care (CC) services in the country since the 1980s with a sustained growth in this field over the last few years. Aims: This review aims to describe CC pharmacy services in Saudi Arabia by exploring the historical evolution of patient care, education, research, and leadership, including challenges and opportunities for professional advancement. Materials and methodology: We reviewed existing literature regarding CC pharmacy services in SA in addition to documented phone interviews with CC pharmacy pioneers in SA. Results: Critical care pharmacy services improved in many facets. We identified possible areas for improvement and suggested an action plan for other countries to expand their CC pharmacy services. Conclusion: In Saudi Arabia, clinical pharmacy services are growing with sustained growth in CC pharmacy services.